Morphological changes of liver and spleen under the impact of dextran-polyacrylamide polymers and their effects as carriers of silver and gold nanoparticles - Kaleinikova О.М.; Kurovska V.О.; Byelinska І.V.; Kutsevol , N.V.; Blashkiv Т.V. (Medicni Perspektivi, 2023)
The possibility of usage of polymer nanocomposites is being intensively studied today with a purpose of their application in medicine, espessialy in oncology. At the experimental stage it is important to determine the mechanisms of the influence of such compounds on the body and their own possible undesirable effects. Aim – to study the effect of the treatment with maximal doses of the dextran-polyacrylamide polymers and their effect as carriers of silver and gold nanoparticles on the spleen and liver. Histological examination of micropreparations of the spleen and liver by the standard method with hematoxylin-eosin staining was made. As a result of the treatment with nonionic (D-g-PAA) and anionic (D-g-PAA (PE)) polymer matrices, changes which occurred in the spleen indicate an increase in the production of all blood cells. These phenomena were absent when silver and gold nanoparticles were included in the matrix. In the liver, treatment with D-g-PAA and D-g-PAA (PE) caused a disorder of hepatic circulation, focal infiltration by inflammatory cells and death of hepatocytes by necrosis. The addition of nanoparticles triggered other mechanisms of alteration, which manifested themselves in excessive accumulation of glycogen, fatty infiltration of hepatocytes, and cell death, mainly through apoptosis. However, along with this, signs of an incomplete regenerative response of the liver were revealed. Morphological changes caused by the treatment with maximal doses of the tested substances indicate their toxic effect, especially on the liver. Further researches are needed to establish the optimal doses and the frequency of their administration, which can be used for therapeutic purposes, including the interaction of studied polymers with blood cells.